Enhancement on dielectric properties of dried banana leaves with sand composites for dielectric resonator antenna - Zulkifli, N.A.; Hoon, W.F.; Ibrahim, S.Z.; Warip, M.N.M.; Seng, L.Y.; Seok, Y.B. (2018)
Dielectric resonator antenna (DRA) is a radio antenna mostly used at microwave frequencies and higher. Ceramic are the material that is usually used in DRA application. This paper introduced dried banana leaves and sand to replace the ceramic material. This DRA application demands for high level antenna performance. The existing materials for DRA is expensive and does not environmental friendly. To cope this problems, the analysis of dried banana leaves with sand composites is evaluated. Dried banana leaves are one of the agricultural residues in Malaysia. The leftover of the agricultural waste that is not being used could endangered the environment and human health. The performance of dried banana leaves and dried banana leaves with sand were studied in the range between 1-3 GHz suitable for dielectric resonator antenna application. Besides, dried banana leaves were mixed with Epoxy Der 331 and Polyamine Clear Hardener in order to analyse the dielectric properties measurement. Finely sand is added to the dried banana leaves to have increment of dielectric constant reading. The measurement results for both sample is obtained.